Multimodal metadiscourse in digital academic journals on linguistics, engineering and medicine - Carrió-Pastor, María Luisa (European journal of English studies, 2021)
The main objectives of this study are, first, to analyse the interactive metadiscourse devices used in engineering, medicine and linguistics and the identities represented; second, to identify the visual metadiscourse elements employed in the three identities constructed in the three specific settings and, finally, to classify and compare the multimodal metadiscourse used to cohere the different parts of digital academic discourse with the aim of guiding the reader textually as well as visually. To this end, academic papers were collected from journals which belonged to the specific fields of linguistics, engineering and medicine. The corpus was analysed to identify and classify the data. The results showed that there were in fact differences in the way academic writers used multimodal metadiscourse and constructed and represented their identity. The study revealed that engineers used visual metadiscourse more frequently, while linguistic researchers preferred the use of textual metadiscourse. Finally, conclusions were drawn.